Yoga and the Interplay between Attentional Load and Emotion Interference. Issue 1 (August 2015) - Menezes, Carolina B.; Dalpiaz, Natalia R.; Rossi, Nalu T.; De Oliveira, Alcyr A.
This study compared 45 yoga practitioners ( M age = 29.7yr., SD = 6.4) and 45 matched controls ( M age = 29.3yr., SD = 6.2) on the performance of a behavioral task that assessed negative emotion interference during a high- and a low-attentional demand condition, as well as on state and trait anxiety scores. Outcomes were also compared between beginner and advanced practitioners. For the behavioral task, the final sample comprised 36 yoga and 38 control participants. The yoga group presented lower emotion interference in the high attentional condition, compared to the low attentional condition; rated emotional images as less unpleasant, compared to controls; and reported lower state and trait anxiety scores relative to controls. Also, emotion interference in the low attentional condition was lower among advanced practitioners and state anxiety was lower among practitioners attending more than two weekly yoga classes. The results suggested that yoga may help improve self-regulatory skills and lower anxiety. The psychological mechanisms underlying the relationship between yoga and emotion regulation should be further investigated in longitudinal studies.